Integrating the Key Competencies of International Large-Scale Assessment (ILSA) into the Teacher-Education Curriculum in the Philippines - Espinosa, Allen A; Gomez, Ma Arsenia C; Miranda, Praksis A; David, Adonis P; Macahilig, Heidi C; Reyes, Allan S; Cortez, Leah Amor S; Palomar, Brando C; de Vera, Jayson L; Patal, Marvin C; San Juan, Mark Ponce C (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
This study proposes a framework to integrate competencies from various international large-scale assessments (ILSAs) into the program design of a teacher educational institution (TEI) in the Philippines. Using a descriptive-developmental research design, the study examined how ILSA key competencies can be incorporated into the curriculum, along with practices of outcomes-based educational programs at the TEI. Inductive thematic analysis of focus group interviews revealed one overarching program-level theme: using ILSA as a benchmark for curriculum development. At the micro level, four core themes emerged: (1) strengthened content teaching, (2) increased pedagogical content knowledge (PCK) courses, (3) explicit targeting and teaching of ILSA competencies through course-intended learning outcomes (CILOs), and (4) ILSA-like assessments. The study recommends that the Philippine Department of Education (DepEd) and TEIs collaborate to align pre-service teacher training with global literacy standards, ensuring that pre-service teachers are equipped to teach ILSA-recommended skills.